Slang Variations in “Black Eyed Peas” Songs - Frans Marthen (PRAGMATICA : Journal of Linguistics and Literature, 2023)
This article explores the use of sociolinguistic slang in the lyrics of Black Eyed Peas songs. The study employs qualitative research methods to analyze the language variations and unconventional vocabulary present in the music text. By observing and recording the lyrics of several Black Eyed Peas songs, the researcher examines how slang contributes to the appeal and relatability of the group's music. Sociolinguistic slang is seen as a form of informal language that develops within specific social groups, often serving as a means of social identification and solidarity. The study reveals that the Black Eyed Peas incorporate slang to establish a contemporary and informal flavor in their songs, facilitating a connection with their audience. The findings contribute to our understanding of how slang can shape the cultural and linguistic aspects of music, highlighting its role in expressing identity and fostering social connections.